Impact of students' cultural values on the corporate entrepreneurship management linked to social responsibility (2020)
The present study tries to analyse the influence of students' cultural values on corporate entrepreneurship management associated with social responsibility. For that purpose, we adopt a multidisciplinary approach that combines stakeholders' issues, topics about corporate entrepreneurship, and innovation management concepts in a specific context where companies need to solve the stakeholders' needs in a new way. In this sense, and according to the scarce breakthrough about the inclusion of new actors in the corporate entrepreneurship process, we decide to review the literature about innovation - a near concept - that allows the participation of other players, different from employees. To then, define a quantitative sequential methodology that begins with the analysis of the gathered data through a classification tree, and finish with an artificial neural network. The study results find that only 14 of the 58 student's cultural values, impact and predict the corporate entrepreneurship management linked to social responsibility. A finding that we incorporate in a simulator that predicts the student's idea quality in the social responsibility framework, from 14 of their cultural values. Finally, we suggest the future verification of our results, in specific contexts that we do not consider like intellectual property issues, cost savings, and recruitment politics. Copyright © 2020 Inderscience Enterprises Ltd.